Penton blooming, a conserved mechanism of genome delivery used by disparate microviruses - Pavol Bardy; Conor I. W. MacDonald; Paul C. Kirchberger; Huw T. Jenkins; Tibor Botka; Lewis Byrom; Nawshin T. B. Alim; Daouda A. K. Traore; Hannah C. Koenig; Tristan R. Nicholas; Maria Chechik; Samuel J. Hart; et al. (mBio)
ABSTRACT Microviruses are single-stranded DNA viruses infecting bacteria, characterized by T = 1 shells made of single jelly-roll capsid proteins. To understand how microviruses infect their host cells, we have isolated and studied an unusually large microvirus, Ebor. Ebor belongs to the proposed “Tainavirinae” subfamily of Microviridae and infects the model Alphaproteobacterium Rhodobacter capsulatus. Using cryogenic electron microscopy, we show that the enlarged capsid of Ebor is the result of an extended C-terminus of the major capsid protein. The extra packaging space accommodates genes encoding a lytic enzyme and putative methylase, both absent in microviruses with shorter genomes. The capsid is decorated with protrusions at its 3-fold axes, which we show to recognize lipopolysaccharides on the host surface. Cryogenic electron tomography shows that during infection, Ebor attaches to the host cell via five such protrusions. This attachment brings a single pentameric capsomer into close contact with the cell membrane, creating a special vertex through which the genome is ejected. Both subtomogram averaging and single particle analysis identified two intermediates of capsid opening, showing that the interacting penton opens from its center via the separation of individual capsomer subunits. Structural comparison with the model Bullavirinae phage phiX174 suggests that this genome delivery mechanism may be widely present across Microviridae.IMPORTANCETailless Microviridae bacteriophages are major components of the global virosphere. Notably, microviruses are prominent members of the mammalian gut virome, and certain compositions have been linked to serious health disorders; however, a molecular understanding of how they initiate infection of their host remains poorly characterized. We demonstrate that trimeric protrusions located at the corners of a single microvirus capsomer mediate host cell attachment. This interaction triggers opening of the capsomer, driven by separation of subunits from its center, much like flower petals open during blooming. This extensive opening explains how the genome translocation apparatus, along with the genome itself, is able to exit the capsid. “Penton blooming” likely represents a conserved mechanism shared by diverse viruses possessing similar capsid architectures.